Experiences of Individuals Awaiting Lung Transplantation. - Skogeland, Ulrika (Respiratory Care, 2018)
Lung transplantation is an established intervention for patients with advanced and life-threatening respiratory disease. Unfortunately, the shortage of organ donors results in a need for organs that greatly exceeds availability. This narrative review aimed to investigate the experiences of patients with respiratory diseases who wait for lung transplantation. Articles were retrieved from medical literature databases. Thirteen qualitative studies were reviewed, one of them used a mixed method. We found that individuals faced varied and complex situations differently while waiting for lung transplantations, depending on physical, psychological, social, and existential factors. Waiting gives hope for a future without the limitations imposed by the disease but also causes great stress. Many individuals struggled with the existential guilt associated with the privilege of having access to transplantation. This review highlighted that support from health-care professionals, next of kin, patients who had previously received a transplantation, and close friends have a vital role to play for individuals waiting for a lung transplantation.